Analysis of Mut'ah Marriage Representation in the Film Bidaah: A Critical Examination of Its Alignment with Islamic Family Law - Mega Sylvia; Suprihatin; Musyaffa Amin Ash Shabah; Agus Supriyanto (Rayah Al-Islam, 2026)
This study aims to analyse the representation of mut'ah marriage practices in the film Bidaah and assess its compatibility with the principles of Islamic family law. This phenomenon is motivated by the emergence of religious practice deviations and the manipulation of religious arguments by charismatic figures depicted in visual media. The focus of this study is how the film constructs the practice of mut'ah marriage and how Islamic family law views this representation. This research method is qualitative with a media text analysis type of research. The data collection technique uses content analysis of the film Bidaah as the primary data source, supported by a literature study as secondary data for its legal basis. The analysis was conducted descriptively and analytically with reference to classical Islamic literature, the Compilation of Islamic Law, and the principles of maqāṣid al-syarī‘ah. The results of the study show that the practice of mut'ah marriage in the film Bidaah is represented as a temporary and deviant ‘inner marriage’. The practice is carried out without the involvement of a guardian, without valid witnesses, and without official registration, with the dowry being only a recitation of Al-Fatihah. From the perspective of Islamic family law, this practice is considered invalid because it does not fulfil the pillars and requirements of marriage and contradicts the sacred purpose of marriage to form a permanent family. This study concludes that the film serves as a social critique of the abuse of authority or power by religious leaders or heads of religion, which can harm the rights of women and children when such marriages occur.